2020
DOI: 10.3390/met10070940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Welding Parameters on Friction Stir Welded Ti–6Al–4V Joints: Temperature, Microstructure and Mechanical Properties

Abstract: In this study, friction stir welding (FSW) of 2-mm-thick Ti–6Al–4V alloy plates was performed using a newly designed friction tool—and the effect of rotation speed and welding speed on microstructure and mechanical properties of the joints were investigated. A simulation model for FSW temperature field calculation was developed, and the effect of rotation speed and welding speed on the temperature field was investigated by experimental and numeric methods. The results show that the rotation speed has a dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…References [8] and [19] in the FSW process parameters indicated that the selected FWS liquid cooled radiator panel material is 6061T6 aluminum alloy under a set of the simulated rotational speed of 1000 r/min, the welding speed of 2 mm/s, and shaft downward pressure of 8000 N. Heat in the entire welding process is mainly concentrated in the weld area [30], and the surface temperature is shown in figure 8. The highest temperature is concentrated in the shoulder area of the stirring tool, and the temperature area spreads in a circular pattern from the shoulder to the surrounding area.…”
Section: Temperature Field Simulation Resultsmentioning
confidence: 99%
“…References [8] and [19] in the FSW process parameters indicated that the selected FWS liquid cooled radiator panel material is 6061T6 aluminum alloy under a set of the simulated rotational speed of 1000 r/min, the welding speed of 2 mm/s, and shaft downward pressure of 8000 N. Heat in the entire welding process is mainly concentrated in the weld area [30], and the surface temperature is shown in figure 8. The highest temperature is concentrated in the shoulder area of the stirring tool, and the temperature area spreads in a circular pattern from the shoulder to the surrounding area.…”
Section: Temperature Field Simulation Resultsmentioning
confidence: 99%
“…Using incorrect welding parameters in friction stir welding can affect the quality of the weld and increase the likelihood of cracking. This is the case, for example, if an excessively high welding speed is used, which can increase the probability of thermal cracking [40]. In addition to the above features, the SEM images showed the presence of WC and ZrC particles on the fracture surfaces.…”
Section: Fracture Analysismentioning
confidence: 95%
“…In the present work, only two parameters, i.e., speed and feed, are varied in the study of the properties. Impact of tool speeds on microstructure and mechanical attributes on Ti-6Al-4V joints, and the optimal range is between 400 and 600 rpm, coupled with a feed rate of 75 mm/min [11]. Tool shoulder diameters between 18 to 24 mm will produce defect-free zones in 6 mm thick plates of AZ31B magnesium alloy for different process parameter combinations [12].…”
Section: Figure 1 Schematic Diagram Of Friction-stir Processingmentioning
confidence: 99%